Translation Shift From Balinese Into English in the Puppet Shadow Script Lubdaka - Sayani, Sayani (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 25 No 1 (2018): MaretDO - 10.24843/ling.2018.v25.i01.p02, 2018)
Balinese and English have different grammatical structure and English does not have speech level like Balinese. The condition may cause both linguistic and cultural shifts to make the translation equivalent. This difference becomes a challenge for translators in finding the closest natural equivalent of Balinese terms of address in English or vice versa. This study analyzed types of shifts in translation occurred in the translation of the terms of address from Balinese into English in puppet shadow script ‘Lubdaka’. This study belonged to qualitative study approach and used descriptive method. The primary data is the translation of terms of address from Balinese into English directly taken from puppet shadow script and its translation into English of the Lubdaka story in the book The Invisible Mirror of Siwaratri Kalpa (2008). Shifts in translation in the data occurred in grammatical (transposition) and in point of view (modulation). There are four types of shifts that belong to the grammatical: structure shift, class shift, unit shift, and intra-system shift. Meanwhile, there are three types of shifts found that belongs to the shift in point of view: lexical dense shift, lexical loose shift, and emphasizing on 2 nd person.